ChemInform Abstract: Copper‐Catalyzed Oxidative Electrophilic Carbofunctionalization of Acrylamides for the Synthesis of Oxindoles. Issue 10 (March 2015) - Li, Xueqin; Xu, Jian; Zhang, Pengbo; Gao, Yuzhen; Wu, Ju; Tang, Guo; Zhao, Yufen
Abstract Transformation of the reaction conditions to the synthesis of a tetrahydroquinoline derivative starting from N‐methyl‐N‐phenylcinnamide fails.